Measurement of the associated production of a Z boson with charm or bottom quark jets in proton-proton collisions at √s=13 TeV; Physical Review D; Vol. 102, iss. 3 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen